2000
DOI: 10.1074/jbc.275.17.12763
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Functional Analysis of the Interaction between von Willebrand Factor A1 Domain and Glycoprotein Ibα

Abstract: Binding of the von Willebrand factor (vWF) A1 domain to the glycoprotein (GP) Ib-IX-V complex mediates platelet adhesion to reactive substrates under high shear stress conditions, a key event in hemostasis and thrombosis. We have now used the known three-dimensional structure of the A1 domain to model the interaction with the GP Ib␣ sequence 271-279, which has previously been implicated in ligand binding. Docking procedures suggested that A1 domain residues in strand ␤3 and preceding loop (residues 559 -566) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…These mutations include those generating type 2M von Willebrand disease (VWF database) and those shown in different studies to abolish platelet interactions with the VWF A1 domain in flow. 16,19,20 The present localization of these mutations on the VWF A1 domain supports the model proposed by Vasudevan et al 16 Among the 21 mutated residues identified, 14 are located at the front of the A1 domain. Eleven of these frontal mutations were located either in strand ␤3 and flanking loops (His559Phe, Asp560Arg, Gly561Ser/Ala, His563Thr, Tyr565Ala, and Lys572Ala) or in helix ␣3 and flanking loops (Glu596Ala, Lys599Thr, Gln604Arg, Phe606Ile, and Ser607Arg).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…These mutations include those generating type 2M von Willebrand disease (VWF database) and those shown in different studies to abolish platelet interactions with the VWF A1 domain in flow. 16,19,20 The present localization of these mutations on the VWF A1 domain supports the model proposed by Vasudevan et al 16 Among the 21 mutated residues identified, 14 are located at the front of the A1 domain. Eleven of these frontal mutations were located either in strand ␤3 and flanking loops (His559Phe, Asp560Arg, Gly561Ser/Ala, His563Thr, Tyr565Ala, and Lys572Ala) or in helix ␣3 and flanking loops (Glu596Ala, Lys599Thr, Gln604Arg, Phe606Ile, and Ser607Arg).…”
Section: Discussionsupporting
confidence: 74%
“…Based on the GPIb␣-peptide docking model, 16 residues Gly561, Tyr565, Glu596, and Lys599 were claimed to play a direct role in GPIb binding. These residues are represented in Figure 8A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our understanding of the molecular basis of platelet adhesion via the interaction of the GPIb/XI/V complex with VWF has advanced primarily through the use of purified fragments of the GPIba and the A1 domain of VWF. 16,17,34 For this reason, the observation that the translocation velocity of platelets over the A1A2A3 domains protein was lower than over the single A1 domain was intriguing and unexpected. .…”
Section: Discussionmentioning
confidence: 99%